PENGARUH LUAS LAHAN, TEKNOLOGI DAN PELATIHAN TERHADAP PENDAPATAN PETANI PADI DI GAMPONG CEMPEUDAK KECAMATAN KUTA MAKMUR ACEH UTARA - Eka Chyntia; maisyuri; fauzan (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2021)
This study aims to examine the effect of land area, technology and training on the income of rice farmers in Gampong Cempeudak, Kuta Makmur District, North Aceh. The data used in this research is secondary data as much as 50 samples using purposive sampling method. The method used to analyze the independent variable and the dependent variable is multiple linear regression method and classical assumption test. The results of the study that partially the variable of land area has a significant effect on the income of rice farmers in Gampong Cempeudak, Kuta Makmur Aceh Utara District, technology has no effect on the income of rice farmers in Gampong Cempeudak, Kuta Makmur District, Aceh Utara, and training has a significant effect on the income of rice farmers in Gampong Cempeudak District Kuta Makmur Aceh Utara. Simultaneously, it shows that land area, technology and training have a significant effect on the income of rice farmers in Cempeudak Village, Kuta Makmur District, North Aceh.